Carbon dynamics related to tree planting on new areas in Norway - Bjart Holtsmark (Statistics Norway, Research Department, 2016)
Extensive tree planting on new areas has been suggested as a climate policy measure in Norway. This paper presents some preliminary calculations related to carbon dynamics of such a measure when the tree planting takes place on areas with relative young birch forests. The main finding, which is robust to several sensitivity analyses, is that after the tree planting project has been initiated, there will be a period of approximately 25 - 30 years with increased accumulation of CO2 in the atmosphere. The reason is that clear cutting of existing vegetation and treeplanting initially will give a significant pulse emission. However, after that initial period with increased accumulation of CO2 in the atmosphere, the project will lead to reduced accumulaiton of CO2, due to the growth of the new trees and the corresponding carbon capture. This is also a robust result.
Keywords: Q23; Q42; Q54; 330; Tree planting; Birch; Spruce; climate; carbon